1997
DOI: 10.1038/ng0697-191
|View full text |Cite
|
Sign up to set email alerts
|

The autosomal recessive isolated deafness, DFNB2, and the Usher 1B syndrome are allelic defects of the myosin-VIIA gene

Abstract: Hereditary non-syndromic profound deafness affects about 1 in 2000 children prior to language acquisition. In 80% of the cases, the mode of transmission is autosomal recessive. The number of genes involved in these recessive forms of isolated deafness (DFNB genes) has been estimated to between 30 and 100. So far, ten DFNB genes have been mapped to human chromosomes, one of which has been isolated. By linkage analysis of a single family whose members were affected with profound deafness, some of them presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
210
1
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(217 citation statements)
references
References 27 publications
2
210
1
4
Order By: Relevance
“…Patients with USH1 are congenitally deaf, have vestibular dysfunction, and develop retinitis pigmentosa (Smith et al 1994). Both genes have also been shown to underlie nonsyndromic forms of deafness (Liu et al 1997a,b;Weil et al 1997;Bork et al 2001). Recently, Myo7a and Cdh23 were both shown to bind to harmonin suggesting that these molecules form a functional complex within the stereocilia (Boeda et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with USH1 are congenitally deaf, have vestibular dysfunction, and develop retinitis pigmentosa (Smith et al 1994). Both genes have also been shown to underlie nonsyndromic forms of deafness (Liu et al 1997a,b;Weil et al 1997;Bork et al 2001). Recently, Myo7a and Cdh23 were both shown to bind to harmonin suggesting that these molecules form a functional complex within the stereocilia (Boeda et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the possibility that a single gene underlies both USH2B and DFNB6 should be considered. Such a situation has already been shown for USH1B and DFNB2, 8,15,16 and may also apply to USH1C and DFNB18 4,18 or USH3 and DFNB15, 14,19 which colocalise. In the frame of this hypothesis, a more deleterious mutation for USH2B than for DFNB6 would be expected.…”
Section: Figure 1 Homozygosity By Descent In a Consanguineous Tunisiamentioning
confidence: 89%
“…Indeed, it has been shown that MYO7A, the gene encoding myosin VIIA, is responsible for both USH1B 15 and an isolated form of recessive deafness, DFNB2. 8,16 During this exclusion mapping, linkage was observed with marker AFM198yf2 (locus D3S1289) which is located within the candidate interval defined for DFNB6 at 3p24. 17 Eight microsatellite markers were used to map the USH2 locus involved in Usher syndrome in family Us.…”
Section: Linkage Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, 16 autosomal recessive hearing loss genes (DFNB) have been localized, of which two have been isolated: the unconventional myosin VIIa gene for DFNB2 1,2 and Connexin 26 3 for DFNB1.…”
Section: Introductionmentioning
confidence: 99%